4‐Dimensional computed tomography‐based ventilation and compliance images for quantification of radiation‐induced changes in pulmonary function. Issue 3 (1st April 2019) - Sharifi, Hoda; Brown, Stephen; McDonald, Gary C; Chetty, Indrin J; Zhong, Hualiang
Abstract: Introduction: 4‐Dimensional computed tomography (4DCT)‐based ventilation imaging is a promising technique for evaluating pulmonary function, but lung elasticity and mechanics are usually not part of the ventilation image analysis. In this study we demonstrate a 4DCT‐based imaging technique that can be used to calculate regional lung compliance changes after radiotherapy (RT). Methods: Six lung cancer patients were included in this study. Four of the patients had 4DCT images acquired pre‐RT, 3 and 9 months post‐RT. Ventilation and compliance were calculated from the deformable image registration (DIR) of 4DCTs, performed from the end‐inhale to the end‐exhale breathing phase. Regional compliance was defined as the ratio of volumetric variation and associated stress in each voxel, representing lung elasticity and computed using a FEM‐based framework. Ventilation, compliance and CT density were calculated for all pre‐RT and post‐RT 4DCTs and evaluation metrics were computed. Results: Average CT density changes were 13.6 ± 11.4HU after 3 months and 26.9 ± 15.8HU after 9 months. Ventilation was reduced at 3 months, but improved at 9 months in regions with dose ≥ 35 Gy, encompassing about 10% of the lung volume; compliance was reduced at both time‐points. Radiation dose ≥ 35 Gy caused major change in lung density and ventilation, which was higher than that previously reported in the literature (i.e. 24 Gy). Conclusion: Lung tissue response is diverse with respect to CT density, ventilation and compliance. Combination of ventilation and compliance with CT density could be beneficial for understanding radiation‐induced lung damage and consequently could help develop improved treatment protocols for lung cancer patients.